The Study on Preparation of Silica Using Residue of Oil Shale Residue - Nie L.; Wang T. (Kemija u Industriji, 2015)
Usage of oil shale produces abundant oil shale residue, which may not only directly cause serious pollution to the environment, but also result in a waste of resource. In this paper, acid leaching method and alkali soluble method were compared to obtain the optimum processing conditions for the preparation of white carbon black, which was determined as follows: the mass fraction of NaOH was 8 %, the alkali dissolving time was 5 h, and the reaction temperature was 100 °C. Then the performance characteristics of the obtained white carbon black were analysed by XRD, SEM and IR spectroscopy. The results showed that the product of silica has a particle size between 20 – 30 nm and a purity of 98.4 %. Preparation of the high quality white carbon black might be a good way to make sufficient and reasonable use of oil shale residues, which will bring many environmental and social benefits.